Improving Service Availability of Singleton Software Component: Challenges and Strategies - Shiferaw, Reta; Kuma, Yohanes (My University, 2016)
This study is intended to contribute for higher availability property of stateful singleton components with user sessions lasting significantly long duration. As availability tactic, the study focuses on replication. Management of state synchronization of long lasting stateful user sessions during switchover is among the main challenges of this study. Design research is employed to device a suitable prototype architecture. Via the design research, the challenges are thoroughly analysed, and prototype is designed to incorporate strategies for the challenges. Qualitative research is also undertaken to propose suitable design patterns and object serialization technologies. The prototype is evaluated to observe correctness of long lasting stateful user sessions after switchover is performed among the replicas. In addition, further stress analysis is performed on the prototype to show points of strength and weakest points.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science